A Noval Approach of Altered Cast Technique in Bilateral Partial Maxillectomy Patient with Severely Restricted Mouth Opening. (31st October 2010) - Tripathi, Shuchi; Chand, Pooran; Singh, Raghuwar D.; Siddharth, Ramashankar; Singh, Balendra P.
Abstract : Patients with extensive head and neck injuries due to trauma and/or extensive surgical procedures often exhibit a severely limited ability to open the mouth. For the dentist involved in prosthodontic treatment of such patients, restricted mouth opening commonly leads to compromised impressions and prostheses especially in cases where both hard and soft palatal parts have been resected. In prosthodontic treatment, the loaded impression tray is the largest item requiring intraoral placement. During impression procedures, wide mouth opening is required for proper tray insertion and alignment. This is not possible in patients with restricted mouth opening, so a modification of the standard impression procedure is often necessary to accomplish this fundamental step in the fabrication of a successful prosthesis. An alteration in the final impression procedure was made using altered cast technique for fabricating an obturator prosthesis with soft palate extension, and the result obtained was quite satisfactory.